2018
DOI: 10.1038/s41598-018-26746-1
|View full text |Cite
|
Sign up to set email alerts
|

NaoXinTong Capsules inhibit the development of diabetic nephropathy in db/db mice

Abstract: NaoXinTong Capsule (NXT), a Chinese medicine, is currently used to treat patients with cardiovascular and cerebrovascular diseases. Clinical observations indicate its anti-diabetic functions with unclear mechanisms. Herein, we report the effect of NXT on diabetic nephropathy (DN). Type 2 diabetic db/db mice were treated with NXT for 14 weeks. In the course of treatment, NXT reduced diabetes-increased glucose levels and improved renal functions. At the end of treatment, we found that NXT ameliorated serum lipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 56 publications
(47 reference statements)
0
23
0
Order By: Relevance
“…20160302). The process of model development and drug treatment processes were similar to those used in previous studies with some modifications [23, 25, 26]. Forty male BKS.Cg-Dock7 m +/+ Lepr db /JNju mice (db/db mice, 7 weeks) and eight nondiabetic C57BLKS/J-LepR db/+ mice (db/m + mice, 7 weeks) were purchased from the Model Animal Research Center of Nanjing University (Nanjing, China).…”
Section: Methodsmentioning
confidence: 99%
“…20160302). The process of model development and drug treatment processes were similar to those used in previous studies with some modifications [23, 25, 26]. Forty male BKS.Cg-Dock7 m +/+ Lepr db /JNju mice (db/db mice, 7 weeks) and eight nondiabetic C57BLKS/J-LepR db/+ mice (db/m + mice, 7 weeks) were purchased from the Model Animal Research Center of Nanjing University (Nanjing, China).…”
Section: Methodsmentioning
confidence: 99%
“…Generally, those mechanisms may include metabolism regulation, antioxidation, anti-inflammation, anti-fibrosis, and podocyte protection, which are thoroughly discussed below. In addition, a table (Supporting Information Table S2 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 ,…”
Section: Mechanisms Involved In the Protective Effects Of Chinese Medicines Against Dnmentioning
confidence: 99%
“… 2018 ; Yang et al. 2018 ). Previous studies found that NXT has resulted in a decreased M1/M2 macrophage ratio and shown that NXT plays an essential role in inhibiting neutrophil migration and injury amplification (Wang et al.…”
Section: Introductionmentioning
confidence: 99%